2018
DOI: 10.1016/j.diabres.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in women with an early diagnosis of gestational diabetes mellitus

Abstract: Women diagnosed with GDM before 24 weeks have unique features, are at risk for adverse outcomes, and require targeted approaches to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…When differences in maternal characteristics and glycemic control were adjusted, there is still a higher risk of preeclampsia in earlier diagnosis group (odds ratio, 2.4; 95% CI, 1.5, 3.8). Similar results were reported in the study of Maisa N et al [16]. In contrast with women who received a diagnosis for GDM at or after 24 weeks, women diagnosed with GDM before 24 weeks were associated with an increased risk for macrosomia (OR 2, 95% 1-4.15, p = 0.0498), but relationship with other adverse outcomes was not found.…”
Section: Discussionsupporting
confidence: 88%
“…When differences in maternal characteristics and glycemic control were adjusted, there is still a higher risk of preeclampsia in earlier diagnosis group (odds ratio, 2.4; 95% CI, 1.5, 3.8). Similar results were reported in the study of Maisa N et al [16]. In contrast with women who received a diagnosis for GDM at or after 24 weeks, women diagnosed with GDM before 24 weeks were associated with an increased risk for macrosomia (OR 2, 95% 1-4.15, p = 0.0498), but relationship with other adverse outcomes was not found.…”
Section: Discussionsupporting
confidence: 88%
“…However, the authors of the IOM guidelines predicted difficulties identifying the causal ordering between GWG and disorders that develop during pregnancy, like GDM, and also advised that conditions diagnosed early in pregnancy and managed effectively, may have reduced risk. As predicted, studies evaluating the effect of GWG on GDM has been shown risks to be both increased [23] and decreased [24] The Committee also accurately predicted that treatment for the condition would alter the pattern of weight gain after diagnosis [25, 26]. More recent studies have evaluated GWG prior to early screening and shown that early in pregnancy, increased GWG does precede the diagnosis of GWG [2729].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined these adverse outcomes of high-risk women [12][13][14][15][16][17]. A recent Australian study concluded that despite early diagnosis, high-risk women suffered higher rates of preterm delivery, cesarean delivery, preeclampsia, and macrosomia, even a er excluding diabetes in pregnancy [12].…”
Section: Discussionmentioning
confidence: 99%